A fiber-reinforced wear-resistant TPU composite material and preparation method thereof

By adding modified aramid fibers and stabilizers to the TPU material, the problems of poor aging resistance and insufficient wear resistance are solved, which significantly improves its toughness and light stability performance, and improves wear resistance and flame retardant performance.

CN118562283BActive Publication Date: 2025-02-07NANTONG SUNCHI RUBBER PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410962574.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-02-07
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

TPU materials have problems such as poor aging resistance, insufficient hardness, poor wear resistance and insufficient elasticity and toughness, which limits their application.

Method used

By adding modified aramid fibers and stabilizers, the strength, rigidity and toughness of the TPU composite material are improved, and the wear resistance is improved through white carbon black, and the flame retardant performance is improved through composite flame retardant.

Benefits of technology

It significantly improves the toughness and light stability of TPU composite materials, while improving its wear resistance and flame retardant properties, and expanding its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The present invention relates to the field of polymer materials, and discloses a fiber-reinforced wear-resistant TPU composite material and a preparation method thereof. The fiber-reinforced wear-resistant TPU composite material comprises the following raw materials in parts by weight: 80-120 parts of thermoplastic polyurethane elastomer, 20-40 parts of modified aramid fiber, 5-8 parts of white carbon black, 1-3 parts of stabilizer, 10-15 parts of cross-linking agent, 3-5 parts of composite flame retardant, and 4-6 parts of lubricant. The modified aramid fiber is a carbon nanotube-modified hybrid aramid fiber, and the carbon nanotube accounts for 0.5-2% of the total mass of the aramid fiber matrix. The present invention can improve the strength and rigidity of the TPU composite material by adding the modified aramid fiber, greatly improve its toughness, and greatly improve the light stability of the material by adding the stabilizer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a fiber-reinforced wear-resistant TPU composite material and a preparation method thereof. Background Art

[0002] TPU (Thermoplastic polyurethanes) is a thermoplastic polyurethane elastomer material, which is a polymer material formed by the reaction of diisocyanate molecules such as diphenylmethane diisocyanate or toluene diisocyanate with macromolecular polyols and low molecular polyols. TPU material has a special soft and hard segment block copolymer structure, high strength and excellent mechanical properties. Compared with other elastic materials, TPU has a wider hardness range and can be reprocessed. TPU products have outstanding load-bearing capacity, impact resistance and shock absorption performance.

[0003] TPU materials have the disadvantage of poor aging resistance, and stabilizers must be added during the processing to inhibit the degradation and cross-linking of TPU. At present, most of the heat stabilizers and light stabilizers used in polymer composite materials are still low-molecular stabilizers. Low-molecular stabilizers are easy to decompose, migrate, and frost when used in polymer materials, thus losing their anti-aging effect. At the same time, existing TPU materials generally have defects such as insufficient hardness, poor wear resistance, and insufficient elasticity and toughness, which limit the application of TPU materials. Summary of the invention

[0004] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a fiber-reinforced wear-resistant TPU composite material and a preparation method thereof. By adding modified aramid fiber, the strength and rigidity of the TPU composite material can be improved, and its toughness can be greatly improved. By adding a stabilizer, the light stability of the material can be greatly improved.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A fiber-reinforced wear-resistant TPU composite material, comprising the following raw materials in parts by weight: 80-120 parts of thermoplastic polyurethane elastomer, 20-40 parts of modified aramid fiber, 5-8 parts of white carbon black, 1-3 parts of stabilizer, 10-15 parts of cross-linking agent, 3-5 parts of composite flame retardant, and 4-6 parts of lubricant;

[0007] The modified aramid fiber is a hybrid aramid fiber modified by carbon nanotubes. The carbon nanotubes account for 0.5-2% of the total mass of the aramid fiber matrix. The hybrid aramid fiber is a copolymerized polyimide fiber containing an imidazole heterocycle, and its structural formula is as follows:

[0008] ;

[0009] The stabilizer is obtained by copolymerizing styrene with 2,4-dihydroxybenzophenone, 2,2,6,6-tetramethylpiperidinol and dimethyl-(E)-stilbene-4,4-oxalate after an ester exchange reaction. The structural formula of the stabilizer is as follows:

[0010] .

[0011] Further preferably, the crosslinking agent is hydroquinone dihydroxyethyl ether or resorcinol dihydroxyethyl ether, the composite flame retardant is ammonium polyphosphate, expanded graphite, and pentaerythritol mixed in a mass ratio of 3:1:2, and the lubricant is one of stearic acid, sodium stearate, paraffin or polyethylene wax.

[0012] Further preferably, the method for preparing the modified aramid fiber comprises the following steps:

[0013] A. Weigh multi-walled carbon nanotubes and ultrasonically dispers them in a 10% HNO3 solution for 20-30 min. Reflux at 120°C for 10-12 h. Filter and wash the dispersion several times. Slowly add the precipitate into the mixed acid and ultrasonically dispers them at room temperature for 1-2 h. Filter and wash the dispersion several times until the pH value of the filtrate reaches 7 to obtain carboxylated multi-walled carbon nanotubes.

[0014] B. uniformly dispersing the carboxylated multi-walled carbon nanotubes in a N,N'-dimethylacetamide / lithium chloride composite solvent, then adding p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole to the dispersion, and then adding 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and reacting under nitrogen protection to obtain a composite spinning solution;

[0015] C. The composite spinning solution containing multi-walled carbon nanotubes in step B is subjected to a spinning process to obtain heterocyclic aramid primary fibers containing multi-walled carbon nanotubes. The primary fibers are subjected to two-stage high-temperature heat treatment to obtain modified aramid fibers.

[0016] Further preferably, the mixed acid in step A is a mixture of 98% H2SO4 and 65% HNO3 in a volume ratio of 3:1.

[0017] More preferably, in step B, the molar ratio of p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole and 3,3',4,4'-benzophenonetetracarboxylic dianhydride is 1:1:2.

[0018] Further preferably, in the two-stage high-temperature heat treatment process in step C, the first stage heat treatment condition is heat treatment at 320-450°C for 1-5 min in a nitrogen environment; the second stage heat treatment condition is heat treatment at 260-300°C for 20-40 min in a nitrogen environment.

[0019] Further preferably, the preparation method of the stabilizer comprises the following steps:

[0020] (1) Add 2,4-dihydroxybenzophenone, dimethyl-(E)-stilbene-4,4-ethanedioate and toluene into a reactor, heat to 45-55°C, stir and dissolve, then add 4% p-toluenesulfonic acid based on the total weight of the monomers, reflux at 100-105°C for 6-10 hours under nitrogen protection, precipitate the product with anhydrous ether, wash several times, and dry to obtain intermediate A;

[0021] (2) Add intermediate A, 2,2,6,6-tetramethylpiperidinol and toluene into a reactor, heat to 60°C and stir to dissolve, then add tetrabutyl titanate, react at 100-105°C for 10-12 hours under nitrogen protection, precipitate the product with anhydrous ether and wash several times, and dry to obtain intermediate B;

[0022] (3) Add intermediate B and styrene to the reactor, then add toluene solvent, pass nitrogen protection, raise the temperature to 75-85°C, add 1% of the total weight of the monomer as initiator dibenzoyl peroxide, react for 20-24 hours, remove the toluene solvent by vacuum distillation, precipitate with anhydrous ether and wash several times, and dry to obtain a stabilizer.

[0023] More preferably, the molar ratio of 2,4-dihydroxybenzophenone, dimethyl-(E)-stilbene-4,4-oxalate and 2,2,6,6-tetramethylpiperidinol is 1:1:1.

[0024] More preferably, the molar ratio of intermediate B to styrene is 1:2-4.

[0025] A method for preparing a fiber-reinforced wear-resistant TPU composite material comprises the following steps:

[0026] S1, adding thermoplastic polyurethane elastomer, modified aramid fiber and crosslinking agent into a high mixing pot and mixing them thoroughly to obtain mixture A, then melting, plasticizing and blending the mixture A through a twin-screw extruder, and extruding and granulating to obtain polymer particles B;

[0027] S2. Add polymer particles B, white carbon black, stabilizer, lubricant and composite flame retardant into a high mixing pot for premixing to obtain mixture C, and then melt and blend the mixture C through a twin-screw extruder, extrude and granulate the mixture, and dry it to obtain a fiber-reinforced wear-resistant TPU composite material.

[0028] Beneficial effects of the present invention:

[0029] The fiber-reinforced wear-resistant TPU composite material of the present invention improves the strength and rigidity of the TPU composite material and greatly improves its toughness by adding modified aramid fiber, improves the light stability of the material by adding a stabilizer, improves the wear resistance of the material by adding white carbon black, and improves the flame retardant property of the material by adding a composite flame retardant.

[0030] Among them, the modified aramid fiber is a carbon nanotube modified hybrid aramid fiber, which is prepared by dispersing carboxylated multi-walled carbon nanotubes in a polymerization solvent of heterocyclic aramid, and then using an in-situ polymerization method to prepare a heterocyclic aramid polymerization solution containing multi-walled carbon nanotubes to achieve the purpose of good dispersion of multi-walled carbon nanotubes in the stock solution, and then by controlling the proportion of polymerization reaction monomers to obtain heterocyclic aramid polymers terminated with different groups. The multi-walled carbon nanotubes are used to play a clamping role, and a large number of heterocyclic aramid molecular chains are effectively passed through the pores in the multi-walled carbon nanotubes, which can improve the tensile strength and Young's modulus of the composite fiber. At the same time, the carboxyl groups on the multi-walled carbon nanotubes can undergo a dehydration condensation reaction with the end groups of the heterocyclic aramid, so that they are cross-linked with the heterocyclic aramid during the high-temperature heat treatment process stage, further improving the modulus of the heterocyclic aramid.

[0031] The stabilizer is obtained by copolymerizing styrene after ester exchange reaction between 2,4-dihydroxybenzophenone, 2,2,6,6-tetramethylpiperidinol and dimethyl-(E)-stilbene-4,4-oxalate. The molecular chain contains benzophenone and hindered amine structure, which have a synergistic effect and can greatly improve the light stability of the material. At the same time, due to the copolymerization with styrene, the molecular weight of the stabilizer is increased, so that the stabilizer can be better compatible with the TPU resin, is not easy to decompose and migrate, and ensures that the material has long-term aging resistance. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1 A modified aramid fiber, the modified aramid fiber is a carbon nanotube modified hybrid aramid fiber, wherein the carbon nanotube accounts for 0.5-2% of the total mass of the aramid fiber matrix, and the hybrid aramid fiber is a copolymerized polyimide fiber containing an imidazole heterocycle, and its structural formula is as follows:

[0034] ;

[0035] The method for preparing the modified aramid fiber comprises the following steps:

[0036] A. Weigh 0.5 g of multi-walled carbon nanotubes and dissolve them evenly in 100 ml of 10% HNO3 solution by ultrasonication for 20-30 min. Reflux at 120°C for 12 h. Filter and wash the dispersion several times. Slowly add the precipitate into 100 ml of a mixed acid solution of 98% H2SO4 and 65% HNO3 in a volume ratio of 3:1. Ultrasonicate at room temperature for 1 h. Filter and wash the dispersion several times until the pH value of the filtrate reaches 7 to obtain carboxylated multi-walled carbon nanotubes.

[0037] B. Dispersing 0.5 g of carboxylated multi-walled carbon nanotubes uniformly in 200 ml of N,N'-dimethylacetamide / lithium chloride composite solvent, adding 10.8 g of p-phenylenediamine, 22.4 g of 2-(4-aminophenyl)-5-aminobenzimidazole, and then adding 64.2 g of 3,3',4,4'-benzophenonetetracarboxylic dianhydride to the dispersion, and reacting under nitrogen protection to obtain a composite spinning solution;

[0038] C. The composite spinning solution containing multi-walled carbon nanotubes in step B is subjected to a spinning process to obtain heterocyclic aramid nascent fibers containing multi-walled carbon nanotubes. The nascent fibers are first heat-treated at 360° C. for 3 min in a nitrogen environment and then heat-treated at 280° C. for 30 min in a nitrogen environment to obtain modified aramid fibers.

[0039] Example 2 A stabilizer is obtained by copolymerizing styrene with 2,4-dihydroxybenzophenone, 2,2,6,6-tetramethylpiperidinol and dimethyl-(E)-stilbene-4,4-oxalate after an ester exchange reaction. The structural formula of the stabilizer is as follows:

[0040] ;

[0041] The preparation method of the above stabilizer comprises the following steps:

[0042] (1) Add 4.2 g of 2,4-dihydroxybenzophenone, 6.1 g of dimethyl-(E)-stilbene-4,4-ethanedioate and 80 ml of toluene into a reactor, heat to 50 °C and stir to dissolve, then add 0.4 g of p-toluenesulfonic acid, reflux at 105 °C under nitrogen protection for 8 h, precipitate the product with anhydrous ether, wash several times, and dry to obtain intermediate A;

[0043] (2) 9.6 g of intermediate A, 3.1 g of 2,2,6,6-tetramethylpiperidinol and 80 ml of toluene were added to a reactor, heated to 60 °C and stirred to dissolve, and then 0.5 g of tetrabutyl titanate was added. The reaction was carried out at 105 °C under nitrogen protection for 12 h. The product was precipitated with anhydrous ether and washed several times, and dried to obtain intermediate B;

[0044] (3) 12.0 g of intermediate B and 6.1 g of styrene were added to the reactor, and then toluene solvent was added. The reactor was protected by nitrogen and heated to 80° C., 0.2 g of dibenzoyl peroxide was added, and the reaction was continued for 22 h. The toluene solvent was removed by vacuum distillation, and the product was precipitated with anhydrous ether and washed several times, and then dried to obtain the stabilizer.

[0045] Example 3 A fiber-reinforced wear-resistant TPU composite material comprises the following raw materials in parts by weight: 120 parts of thermoplastic polyurethane elastomer, 20 parts of modified aramid fiber, 8 parts of white carbon black, 1 part of stabilizer, 15 parts of dihydroxyethyl hydroquinone ether, 1.5 parts of ammonium polyphosphate, 0.5 parts of expanded graphite, 1 part of pentaerythritol, 3 parts of stearic acid, and 3 parts of polyethylene wax; the modified aramid fiber is the carbon nanotube-modified hybrid aramid fiber prepared in Example 1, and the stabilizer is the styrene copolymer prepared in Example 2.

[0046] The method for preparing the above-mentioned fiber-reinforced wear-resistant TPU composite material comprises the following steps:

[0047] S1, adding thermoplastic polyurethane elastomer, modified aramid fiber and hydroquinone dihydroxyethyl ether into a high mixing pot and mixing them thoroughly to obtain a mixture A, then melting, plasticizing and blending the mixture A through a twin-screw extruder, and extruding and granulating to obtain polymer particles B;

[0048] S2. Add polymer particles B, white carbon black, stabilizer, ammonium polyphosphate, expanded graphite, pentaerythritol, stearic acid and polyethylene wax into a high mixing pot for premixing to obtain a mixture C. Then, melt and blend the mixture C through a twin-screw extruder and extrude it into granules. After drying, a fiber-reinforced wear-resistant TPU composite material is obtained.

[0049] Example 4 A fiber-reinforced wear-resistant TPU composite material comprises the following raw materials in parts by weight: 80 parts of thermoplastic polyurethane elastomer, 40 parts of modified aramid fiber, 5 parts of white carbon black, 3 parts of stabilizer, 10 parts of dihydroxyethyl hydroquinone ether, 2.5 parts of ammonium polyphosphate, 0.8 parts of expanded graphite, 1.7 parts of pentaerythritol, 2 parts of sodium stearate, and 2 parts of paraffin; the modified aramid fiber is the carbon nanotube-modified hybrid aramid fiber prepared in Example 1, and the stabilizer is the styrene copolymer prepared in Example 2.

[0050] The method for preparing the fiber-reinforced wear-resistant TPU composite material comprises the following steps:

[0051] S1, adding thermoplastic polyurethane elastomer, modified aramid fiber and resorcinol dihydroxyethyl ether into a high mixing pot and mixing them thoroughly to obtain a mixture A, then melting, plasticizing and blending the mixture A through a twin-screw extruder, and extruding and granulating to obtain polymer particles B;

[0052] S2. Add polymer particles B, white carbon black, stabilizer, ammonium polyphosphate, expanded graphite, pentaerythritol, sodium stearate and paraffin into a high mixing pot for premixing to obtain a mixture C, and then melt and blend the mixture C through a twin-screw extruder, extrude and granulate it, and dry it to obtain a fiber-reinforced wear-resistant TPU composite material.

[0053] Example 5 A fiber-reinforced wear-resistant TPU composite material comprises the following raw materials in parts by weight: 100 parts of thermoplastic polyurethane elastomer, 30 parts of modified aramid fiber, 6 parts of white carbon black, 2 parts of stabilizer, 12 parts of dihydroxyethyl hydroquinone ether, 2 parts of ammonium polyphosphate, 0.7 parts of expanded graphite, 1.3 parts of pentaerythritol, 3 parts of stearic acid, and 2 parts of paraffin; the modified aramid fiber is the carbon nanotube-modified hybrid aramid fiber prepared in Example 1, and the stabilizer is the styrene copolymer prepared in Example 2.

[0054] The method for preparing the fiber-reinforced wear-resistant TPU composite material comprises the following steps:

[0055] S1, adding thermoplastic polyurethane elastomer, modified aramid fiber and hydroquinone dihydroxyethyl ether into a high mixing pot and mixing them thoroughly to obtain a mixture A, then melting, plasticizing and blending the mixture A through a twin-screw extruder, and extruding and granulating to obtain polymer particles B;

[0056] S2. Add polymer particles B, white carbon black, stabilizer, ammonium polyphosphate, expanded graphite, pentaerythritol, stearic acid and paraffin into a high mixing pot for premixing to obtain a mixture C. Then, melt and blend the mixture C through a twin-screw extruder and extrude it into granules. After drying, a fiber-reinforced wear-resistant TPU composite material is obtained.

[0057] Comparative Example 1 A fiber-reinforced wear-resistant TPU composite material comprises the following raw materials in parts by weight: 100 parts of thermoplastic polyurethane elastomer, 6 parts of white carbon black, 2 parts of stabilizer, 12 parts of dihydroxyethyl hydroquinone ether, 2 parts of ammonium polyphosphate, 0.7 parts of expanded graphite, 1.3 parts of pentaerythritol, 3 parts of stearic acid, and 2 parts of paraffin; the stabilizer is the styrene copolymer prepared in Example 2.

[0058] The method for preparing the fiber-reinforced wear-resistant TPU composite material comprises the following steps:

[0059] S1, adding thermoplastic polyurethane elastomer and hydroquinone dihydroxyethyl ether into a high mixing pot and mixing them thoroughly to obtain a mixture A, then melting, plasticizing and blending the mixture A through a twin-screw extruder, and extruding and granulating to obtain polymer particles B;

[0060] S2. Add polymer particles B, white carbon black, stabilizer, ammonium polyphosphate, expanded graphite, pentaerythritol, stearic acid and paraffin into a high mixing pot for premixing to obtain a mixture C. Then, melt and blend the mixture C through a twin-screw extruder and extrude it into granules. After drying, a fiber-reinforced wear-resistant TPU composite material is obtained.

[0061] Comparative Example 2 A fiber-reinforced wear-resistant TPU composite material comprises the following raw materials in parts by weight: 100 parts of thermoplastic polyurethane elastomer, 30 parts of modified aramid fiber, 6 parts of white carbon black, 12 parts of dihydroxyethyl hydroquinone, 2 parts of ammonium polyphosphate, 0.7 parts of expanded graphite, 1.3 parts of pentaerythritol, 3 parts of stearic acid, and 2 parts of paraffin; the modified aramid fiber is the carbon nanotube-modified hybrid aramid fiber prepared in Example 1.

[0062] The method for preparing the fiber-reinforced wear-resistant TPU composite material comprises the following steps:

[0063] S1, adding thermoplastic polyurethane elastomer, modified aramid fiber and hydroquinone dihydroxyethyl ether into a high mixing pot and mixing them thoroughly to obtain a mixture A, then melting, plasticizing and blending the mixture A through a twin-screw extruder, and extruding and granulating to obtain polymer particles B;

[0064] S2, adding polymer particles B, white carbon black, ammonium polyphosphate, expanded graphite, pentaerythritol, stearic acid and paraffin into a high mixing pot for premixing to obtain a mixture C, and then melting and blending the mixture C through a twin-screw extruder, extruding and granulating, and drying to obtain a fiber-reinforced wear-resistant TPU composite material.

[0065] Performance Testing

[0066] 1. Mechanical properties test

[0067] The fiber-reinforced wear-resistant TPU composite materials prepared in Examples 3 to 5 and Comparative Examples 1 to 2 were processed into corresponding specimens for the following mechanical property tests. Referring to GB / T 528-2009, the specimens were cut into dumbbell-shaped tensile specimens of 25 mm×4 mm, with a tensile rate of 20 mm / min, and tensile strength and impact strength tests were performed using a universal testing machine. Referring to GB / T 9867-2008, the specimens were cut into cylindrical shapes with a Φ×h of 16 mm×10 mm, and DIN abrasion tests were performed using a DN abrasion machine. The experimental data are shown in Table 1.

[0068] Table 1 Mechanical properties of fiber reinforced wear-resistant TPU composites

[0069]

[0070] As can be seen from the data in Table 1, the tensile strength of the fiber-reinforced wear-resistant TPU composite material in Comparative Example 1 is significantly lower than that of other groups, indicating that the addition of modified aramid fiber can improve the strength and rigidity of TPU and greatly improve its toughness. The modified aramid fiber of the present invention is a carbon nanotube-modified hybrid aramid fiber. By dispersing carboxylated multi-walled carbon nanotubes in the polymerization solvent of heterocyclic aramid, and then using an in-situ polymerization method to prepare a heterocyclic aramid polymer solution containing multi-walled carbon nanotubes to achieve the purpose of good dispersion of multi-walled carbon nanotubes in the stock solution, and then by controlling the ratio of polymerization reaction monomers, heterocyclic aramid polymers with different group terminations are obtained. Multi-walled carbon nanotubes are used to play a clamping role, and a large number of heterocyclic aramid molecular chains are effectively passed through the holes in the multi-walled carbon nanotubes, which can improve the tensile strength and Young's modulus of the composite fiber. At the same time, the carboxyl groups on the multi-walled carbon nanotubes can undergo a dehydration condensation reaction with the end groups of the heterocyclic aramid, so that they are cross-linked with the heterocyclic aramid in the high-temperature heat treatment process stage, further improving the modulus of the heterocyclic aramid. In Comparative Example 2, no stabilizer was added, which had little effect on the mechanical properties of the fiber-reinforced wear-resistant TPU composite material.

[0071] 2. Light stability test

[0072] The fiber-reinforced wear-resistant TPU composite materials prepared in Examples 4 to 6 and Comparative Examples 1 to 2 were cut into 30 mm × 30 mm specimens, placed in a UV light box for accelerated aging, and subjected to a light stability test. The tensile strength was tested at a rate of 5 mm / min every 10 hours. The tensile strength retention rate was calculated by comparing with the initial tensile strength. The data are shown in Table 2 below.

[0073] Table 2 Light stability of fiber-reinforced wear-resistant TPU composites

[0074]

[0075] It can be seen from the data in Table 2 that the decrease in tensile strength of the fiber reinforced wear-resistant TPU composite material in Comparative Example 2 after UV accelerated aging is greater than that of other groups, indicating that the light stability of the material without adding a stabilizer is worse than that of other groups. The stabilizer of the present invention is obtained by copolymerizing styrene with 2,4-dihydroxybenzophenone, 2,2,6,6-tetramethylpiperidinol and dimethyl-(E)-stilbene-4,4-oxalate after an ester exchange reaction. The molecular chain contains benzophenone and a hindered amine structure, and the two have a synergistic effect, which can greatly improve the light stability of the material. At the same time, due to the copolymerization with styrene, the molecular weight of the stabilizer is increased, so that it can be better compatible with the TPU resin, and it is not easy to decompose and migrate, ensuring that the material has long-term aging resistance.

[0076] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A fiber-reinforced wear-resistant TPU composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 80-120 parts of thermoplastic polyurethane elastomer, 20-40 parts of modified aramid fiber, 5-8 parts of white carbon black, 1-3 parts of stabilizer, 10-15 parts of cross-linking agent, 3-5 parts of composite flame retardant, and 4-6 parts of lubricant; The modified aramid fiber is a carbon nanotube modified hybrid aramid fiber, the carbon nanotube accounts for 0.5-2% of the total mass of the aramid fiber matrix, and the hybrid aramid fiber is a copolymerized polyimide fiber containing an imidazole heterocycle, and its structural formula is as follows: , The preparation method of the modified aramid fiber comprises the following steps: A. Weigh multi-walled carbon nanotubes and ultrasonically dispers them in a 10% HNO3 solution for 20-30 min. Reflux at 120°C for 10-12 h. Filter and wash the dispersion several times. Slowly add the precipitate into the mixed acid and ultrasonically dispers them at room temperature for 1-2 h. Filter and wash the dispersion several times until the pH value of the filtrate reaches 7 to obtain carboxylated multi-walled carbon nanotubes. B. uniformly dispersing the carboxylated multi-walled carbon nanotubes in a N,N'-dimethylacetamide / lithium chloride composite solvent, then adding p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole to the dispersion, and then adding 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and reacting under nitrogen protection to obtain a composite spinning solution; C. The composite spinning solution containing multi-walled carbon nanotubes in step B is subjected to a spinning process to obtain heterocyclic aramid primary fibers containing multi-walled carbon nanotubes, and the primary fibers are subjected to two-stage high-temperature heat treatment to obtain modified aramid fibers; The stabilizer is obtained by copolymerizing styrene after ester exchange reaction between 2,4-dihydroxybenzophenone, 2,2,6,6-tetramethylpiperidinol and dimethyl-(E)-stilbene-4,4-oxalate. The structural formula of the stabilizer is as follows: 。 2. The fiber-reinforced wear-resistant TPU composite material according to claim 1, characterized in that: The crosslinking agent is hydroquinone dihydroxyethyl ether or resorcinol dihydroxyethyl ether, the composite flame retardant is ammonium polyphosphate, expanded graphite, and pentaerythritol mixed in a mass ratio of 3:1:2, and the lubricant is one of stearic acid, sodium stearate, paraffin or polyethylene wax.

3. The fiber-reinforced wear-resistant TPU composite material according to claim 1, characterized in that: The mixed acid in step A is a mixture of 98% H2SO4 and 65% HNO3 in a volume ratio of 3:

1.

4. The fiber-reinforced wear-resistant TPU composite material according to claim 1, characterized in that: In the step B, the molar ratio of p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole and 3,3',4,4'-benzophenonetetracarboxylic dianhydride is 1:1:

2.

5. The fiber-reinforced wear-resistant TPU composite material according to claim 1, characterized in that: In the two-stage high-temperature heat treatment process in step C, the first stage heat treatment condition is heat treatment at 320-450° C. for 1-5 min in a nitrogen environment; the second stage heat treatment condition is heat treatment at 260-300° C. for 20-40 min in a nitrogen environment.

6. The fiber-reinforced wear-resistant TPU composite material according to claim 1, characterized in that: The preparation method of the stabilizer comprises the following steps: (1) Add 2,4-dihydroxybenzophenone, dimethyl-(E)-stilbene-4,4-ethanedioate and toluene into a reactor, heat to 45-55°C, stir and dissolve, then add 4% p-toluenesulfonic acid based on the total weight of the monomers, reflux at 100-105°C for 6-10 hours under nitrogen protection, precipitate the product with anhydrous ether, wash several times, and dry to obtain intermediate A; (2) Add intermediate A, 2,2,6,6-tetramethylpiperidinol and toluene into a reactor, heat to 60°C and stir to dissolve, then add tetrabutyl titanate, react at 100-105°C for 10-12 hours under nitrogen protection, precipitate the product with anhydrous ether and wash several times, and dry to obtain intermediate B; (3) Add intermediate B and styrene into a reactor, then add toluene solvent, pass nitrogen gas for protection, raise the temperature to 75-85°C, add 1% of the total weight of the monomer as initiator dibenzoyl peroxide, react for 20-24 hours, remove the toluene solvent by vacuum distillation, precipitate with anhydrous ether and wash several times, and dry to obtain the stabilizer.

7. The fiber-reinforced wear-resistant TPU composite material according to claim 6, characterized in that: The molar ratio of the 2,4-dihydroxybenzophenone, dimethyl-(E)-stilbene-4,4-oxalate and 2,2,6,6-tetramethylpiperidinol is 1:1:

1.

8. The fiber-reinforced wear-resistant TPU composite material according to claim 6, characterized in that: The molar ratio of the intermediate B to styrene is 1:2-4.

9. A method for preparing a fiber-reinforced wear-resistant TPU composite material, wherein the fiber-reinforced wear-resistant TPU composite material is as described in any one of claims 1 to 8, characterized in that: The following steps are involved: S1, adding thermoplastic polyurethane elastomer, modified aramid fiber and crosslinking agent into a high mixing pot and mixing them thoroughly to obtain mixture A, then melting, plasticizing and blending the mixture A through a twin-screw extruder, and extruding and granulating to obtain polymer particles B; S2. Add polymer particles B, white carbon black, stabilizer, lubricant and composite flame retardant into a high mixing pot for premixing to obtain mixture C, and then melt and blend the mixture C through a twin-screw extruder, extrude and granulate the mixture, and dry it to obtain a fiber-reinforced wear-resistant TPU composite material.

Citation Information

Patent Citations

  • Method for preparing polyimide / carbon nanotube nanocomposite

    CN102702744A

  • Long aramid fiber-reinforced wear-resistant thermoplastic polyurethane (TPU) composite material and preparation method thereof

    CN103819892A